Similarities and Differences of Photosynthesis Establishment Related mRNAs and Novel lncRNAs in Early Seedlings (Coleoptile/Cotyledon vs. True Leaf) of Rice and Arabidopsis - Shi, Yafei; Chen, Jian; Hou, Xin (Frontiers in Genetics, 2020)
Photosynthesis harnesses sunlight to assimilate carbon dioxide and produce the biomass that is essential for all life on earth. In seed plants, leaf is the main organ for photosynthesis and production of organic nutrients. The seeds are mobilized to fuel post-germination seedling growth until seedling photosynthesis can be efficiently established. However, the photosynthesis and metabolism in the early growth and development have not been studied systematically and are still largely unknown. In this study, we used two model plants, rice (Oryza sativa L.; monocotyledon) and Arabidopsis (Arabidopsis thaliana; dicotyledoneae) to determine the similarities and differences in photosynthesis in cotyledons and true leaves during the early developmental stages. The photosynthesis-related genes and proteins, and chloroplast functions were determined through RNA-seq, real-time PCR, western blotting and chlorophyll fluorescence analysis. We found that in rice, the photosynthesis established gradually from coleoptile (cpt), incomplete leaf (icl) to first complete leaf (fcl); whereas, in Arabidopsis, photosynthesis well developed in cotyledon, and the photosynthesis-related genes and proteins expressed comparably in cotyledon (cot), first true leaf (ftl) and second true leaf (stl). Additionally, We attempted to establish an mRNA‐lncRNA signature to explore the similarities and differences in photosynthesis establishment between the two species, and found that DEGs, including encoding mRNAs and novel lncRNAs, related to photosynthesis in three stages have considerable differences between rice and Arabidopsis. Further GO and KEGG analysis systematically revealed the similarities and differences of expression styles of photosystem subunits and assembly factors, and starch and sucrose metabolisms between cotyledons and true leaves in the two species. Our results help to elucidate the gene functions of mRNA‐lncRNA signatures.